Paleoamerican diet, migration and morphology in Brazil: archaeological complexity of the earliest Americans. - Sabine Eggers; Maria Parks; Gisela Grupe; Karl J Reinhard (PLoS ONE, 2011)
During the early Holocene two main paleoamerican cultures thrived in Brazil: the Tradição Nordeste in the semi-desertic Sertão and the Tradição Itaparica in the high plains of the Planalto Central. Here we report on paleodietary singals of a Paleoamerican found in a third Brazilian ecological setting--a riverine shellmound, or sambaqui, located in the Atlantic forest. Most sambaquis are found along the coast. The peoples associated with them subsisted on marine resources. We are reporting a different situation from the oldest recorded riverine sambaqui, called Capelinha. Capelinha is a relatively small sambaqui established along a river 60 km from the Atlantic Ocean coast. It contained the well-preserved remains of a Paleoamerican known as Luzio dated to 9,945±235 years ago; the oldest sambaqui dweller so far. Luzio's bones were remarkably well preserved and allowed for stable isotopic analysis of diet. Although artifacts found at this riverine site show connections with the Atlantic coast, we show that he represents a population that was dependent on inland resources as opposed to marine coastal resources. After comparing Luzio's paleodietary data with that of other extant and prehistoric groups, we discuss where his group could have come from, if terrestrial diet persisted in riverine sambaquis and how Luzio fits within the discussion of the replacement of paleamerican by amerindian morphology. This study adds to the evidence that shows a greater complexity in the prehistory of the colonization of and the adaptations to the New World.